A Suggested Program in the Light of Integration of (TPACK) Patterns and its Effectiveness in Knowledge Management on South Hebron Chemistry Teachers - Irjan, Ibtisam Abduallah; Ismail, Magdy Ragab; Badawy, Rasha Mahmoud; Adas, Mohsen Mahmoud (Journal of Educational and Psychological Sciences, 2021)
The aim of the current research is to investigate the effectiveness of a program based on the integration of patterns of pedagogical and technological knowledge (TPACK) in developing knowledge management processes for chemistry teachers in the South Hebron Directorate in Palestine, and to achieve this, the knowledge management processes to be developed for chemistry teachers have been identified, in addition to proposing a program In light of the integration of patterns of (TPACK), the study used the observation card, Analysis of narrative records of teachers’ documents, and the interview method to measure knowledge management processes for chemistry teachers, and the research sample consisted of (31) teachers from chemistry teachers in the South Hebron District, and the study tools were applied to teachers before and after the implementation of the program. Results The effectiveness of the proposed program considering the (TPACK) approach in developing knowledge management processes for chemistry teachers. The research recommended the necessity of adopting the (TPACK) approach in teacher development and training programs and holding training courses to provide teachers with teaching skills in the context of the TPACK approach and studies related to evaluation and the development of knowledge management processes in the various stages of education.